Analisis Pengaruh Transparansi dan Akuntabilitas terhadap Kepercayaan Publik - Karneji Sumarlin Bucika Sormin; Syahyunan; Rina br. Bukit (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of transparency and accountability on public trust in financial management in the church (a case study on the GKPI Special Congregation Sidorame). The research method used is quantitative with a descriptive approach to determine the extent of the influence of independent variables on dependent variables. The population in this study is the congregation of GKPI Special Congregation Sidorame, and the sample determination technique uses simple random sampling. The data source used is primary data collected through a questionnaire. Data analysis is conducted through descriptive analysis, research instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS version 27. The results of the study explain that (1) transparency has a positive and significant effect on public trust, (2) accountability has a positive and significant effect on public trust, and (3) transparency and accountability simultaneously have a positive and significant effect on public trust.